2021
DOI: 10.3390/su13126613
|View full text |Cite
|
Sign up to set email alerts
|

Employee-Oriented CSR and Unethical Pro-Organizational Behavior: The Role of Perceived Insider Status and Ethical Climate Rules

Abstract: Although existing research generally has found that corporate social responsibility (CSR) has a positive impact on organizations and individuals, researchers should still be alert to the potential risks it may bring. This study will explore why employee-oriented corporate social responsibility (employee-oriented CSR) triggers unethical pro-organizational behavior (UPB). Based on the social identity theory, this study establishes a moderated mediation model to explore the impact mechanism of employee-oriented C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
(101 reference statements)
2
9
0
Order By: Relevance
“…These findings contribute to the existing theory on UPB by confirming the positive links between LMX-UPB [6,15] and organizational identification-UPB [5,9,13,73] in a developing country context. Previous studies have indicated that social exchange and social identity theories may be useful in explaining why employees are involved in UPB.…”
Section: Discussionsupporting
confidence: 77%
“…These findings contribute to the existing theory on UPB by confirming the positive links between LMX-UPB [6,15] and organizational identification-UPB [5,9,13,73] in a developing country context. Previous studies have indicated that social exchange and social identity theories may be useful in explaining why employees are involved in UPB.…”
Section: Discussionsupporting
confidence: 77%
“…Yin et al ( 2021 ) only introduce PIS to explain the mechanism of PP and employee innovative behavior. In future studies, more mechanisms from different viewpoints should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Gimenez et al (2012) indicated that firms must operate cautiously and responsibly, and adopt employee-oriented practices (EoP) and community engagement practices (CEP) to ensure the health and safety of their employees and the quality of life in the local community. EoP provides employees with the proper working conditions, career development and training, a fair working environment, and promotes labor relations and employee participation (Yin et al, 2021). CEP are activities undertaken by companies to collaborate with the community to tackle problems impacting their social well-being (Ni et al, 2015).…”
Section: Sustainable Management Practices 1711mentioning
confidence: 99%